Case Report: Toxigenic Corynebacterium ulcerans Diphtheria-Like Infection in a Horse in the United Kingdom - Zendri, Flavia; Isgren, Cajsa Marie; Sinovich, Matthew; Richards-Rios, Peter; Hopkins, Katie L.; Russell, Katherine; Groves, Natalie; Litt, David; Fry, Norman K.; Timofte, Dorina (Frontiers in Veterinary Science, 2021)
Corynebacterium ulcerans (C. ulcerans) may cause diphtheria in humans and can be carried by a wide range of animal species including dairy cows and, more recently, dogs and cats that have been increasingly involved in zoonotic trasmission. We isolated and characterized, by WGS, a toxigenic C. ulcerans strain from a diseased horse in the United Kingdom showing clinical signs of respiratory diphtheria comparable to those seen in people. Our results indicate a role for horses as reservoirs for zoonotic C. ulcerans.